Bacteriological survey of tuberculous lymphadenitis in South-east England: 1973-80. - Grange, J (1982)
During the eight years 1973-80 the Public Health Laboratory Service Regional Centre for Tuberculosis Bacteriology received cultures of mycobacteria from 2339 patients with tuberculous lymphadenitis. Of these, 2272 were M tuberculosis (2207 human and 65 bovine strains) and 67 were other mycobacterial species, usually M avium and its intracellulare variant. Disease due to the human strains of M tuberculosis occurred most often in young women of Asian ethnic origin. Many bovine strains isolated from Asian patients differ from the classical bovine type in being sensitive to pyrazinamide: the origin of these strains, whether from other people or from cattle, is unknown. Lymphadenitis due to bovine strains tended to occur in an older age group than the human strains and probably include relatively more cases of reactivation diseases. Infection caused by the other mycobacterial species occurred mainly in young children of European origin. Tuberculosis, therefore, remains an important cause of lymphadenopathy in Britain.